The 'heel impact' force peak during running is neither 'heel' nor 'impact' and does not quantify shoe cushioning effects - Shorten, Martyn; Mientjes, Martine I.V. (Footwear science, 2011)
It has been common practice in studies of running shoe cushioning to use the magnitude of the initial transient peak (Fz 1 ) of the vertical ground reaction force (Fz(t)), as an index of heel impact severity. Frequently, the results of such studies have been inconsistent with impact attenuation theory, in vitro impact test results and other load measures. This paper concludes that such use of Fz 1 as a measure of heel impact load is not valid. Fz(t) and in shoe-pressure distributions were recorded while 20 male subjects ran at 4.0 ± 0.2 m/s on a laboratory runway in three footwear conditions representing the approximate range of commercially available running shoes and a minimal, uncushioned control shoe. Pressure data were used to identify spatial (heel and distal foot) components of Fz(t) and spectral analysis was used to distinguish high and low frequency components. Consistent with previous reports, cushioned shoes attenuated Fz 1 magnitude by less than 10% and the most compliant shoe produced significantly higher force peaks than shoes with stiffer cushioning. Analysis of the spatial and frequency components of Fz(t) revealed that Fz 1 is a composite that includes high frequency (heel impact) loads but that low frequency force components originating both in the heel and distal forefoot contribute about half its magnitude. In contrast to Fz 1 , cushioned shoes attenuated the high frequency (impact) force component by 35%, and effects across shoe conditions were consistent with both theory and in vitro impact test results. Thus Fz 1 is neither uniquely defined by heel impact, nor a reliable indicator of impact magnitude. It can be shown that the artifactual effects of cushioning on Fz 1 magnitude are derived from the superimposition of low frequency (non-impact) and non-heel load components.